2020
DOI: 10.1002/adma.202002467
|View full text |Cite
|
Sign up to set email alerts
|

Eppur si Muove: Proton Diffusion in Halide Perovskite Single Crystals

Abstract: Halide perovskites, HaPs, can show remarkable to outstanding properties and photovoltaic (PV) devices in which they are the absorber can show excellent performances. [1-4] Apart from the PV results, also light-emission, radiation detection, and other electronics are explored. [5-8] During their relatively short history, numerous questions have arisen about the materials' properties and functions with many central ones still under discussion, such as the proposed idea of defect tolerance which awaits experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
108
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 60 publications
(115 citation statements)
references
References 74 publications
5
108
2
Order By: Relevance
“…in which the authors investigate the diffusion of protons in methylammonium lead triiodide (MAPI). [ 1 ] In this study, the diffusion of D + in MAPI is reported to be 3 × 10 −10 cm 2 s −1 , which is substantially larger than a previous estimate (1.5 × 10 −15 cm 2 s −1 ). [ 2 ] Based on this, the authors claim that other reports of ion diffusion in HOIP material should be re‐examined to take into account the fast background diffusion of H + .…”
Section: Figurecontrasting
confidence: 64%
See 2 more Smart Citations
“…in which the authors investigate the diffusion of protons in methylammonium lead triiodide (MAPI). [ 1 ] In this study, the diffusion of D + in MAPI is reported to be 3 × 10 −10 cm 2 s −1 , which is substantially larger than a previous estimate (1.5 × 10 −15 cm 2 s −1 ). [ 2 ] Based on this, the authors claim that other reports of ion diffusion in HOIP material should be re‐examined to take into account the fast background diffusion of H + .…”
Section: Figurecontrasting
confidence: 64%
“…Methylammonium lead triiodide single crystals were grown from a solution of CH 3 NH 3 I (1 m ) and PbI 2 (1 m ) in γ‐butyrolactone. [ 1 ] The crystals were collected by gravity filtration, washed with a small volume of γ‐butyrolactone, and air‐dried protected from light. The crystals were selected based on size and placed individually in 2 mL open vials that were sealed in 25 mL vial containing 3 mL of a D 2 O solution of saturated K 2 CO 3 to maintain the relative humidity constant at 43%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, such kinetics should strongly depend on the migration speed of protons, which should also depend on the H 2 O concentration in the perovskite structure. 75,76 5 General discussion: pulling it all together…”
Section: The Role Of Methylaminementioning
confidence: 99%
“… 30 32 However, recent studies also suggest that the influence of A site cations such as Cs + , CH 3 NH 3 + , and (NH 2 ) 2 CH + or even H + should not be neglected. 33 , 34 Overall, it is difficult to find one responsible for the ionic motion in perovskite as it largely depends on the system being studied. Nevertheless, it is clear that mobile ions are present in a large majority of metal halide perovskites and need to be accounted for.…”
mentioning
confidence: 99%